The use of reflective journal in a postgraduate research methodology course: student experiences - Yong, Mei Fung; Tan, Bee Hoon (Universiti Putra Malaysia Press, 2013)
This paper examines the research skill development of an intact group of postgraduate (Master of Arts) students in a research methodology course. Data were collected from the students' weekly introspective reflective journals over one semester and a semi-structured interview at the end of the course. Results from the students' reflections revealed the initial high anxiety among novice researchers who had to juggle between learning new concepts and applying the knowledge in practice. Those who looked at the rewards instead of the challenges found their learning processes more meaningful although they also struggled in completing tasks and writing assignments. The students' esearch skill development culminated in a sense of achievement and satisfaction. The findings from the study contribute to the awareness of the difficulties, the strategies used and the worthwhile learning experiences of novice researchers in acquiring and developing research skills. Suggestions for pedagogy are identified for the use of reflections in the classroom.